(untitled) (Bangladesh Journal of Pharmacology, 2016)
The main objective of the present study was to investigate the anti-tumor activity of corosolic acid in CaSki human cervical cancer cells. Fluorescence and phase contrast microscopic techniques were used to study the effect of the compound on cellular morphology and apoptosis. Results revealed that corosolic acid exerted potent, dose- and time-dependent growth inhibitory effects in CaSki cell proliferation. Cells got detached from one another making clusters of small number of cells floating in the medium. After the cells were treated with 10, 50 and 100 µM concentrations of corosolic acid, cells began to emit orange red fluorescence more heavily at the centre of cells indicating apoptosis. Corosolic acid also induced G2/M cell cycle arrest in a dose-dependent manner. Increasing doses of corosolic acid treatment to these cells resulted in significant and dose-dependent down-regulation of PI3K and Akt protein expressions. Video Clip of Methodology: Western blot assay: 2 min 1 sec Full Screen Alternate